What is the what : the autobiography of Valentino Achak Deng : a novel - Eggers, Dave. (New York : Vintage Books, 2007)
A biographical novel traces the story of Valentino Achak Deng, who as a boy was separated from his family when his village in southern Sudan was attacked, and became one of the estimated 17,000 "lost boys of Sudan" before relocating from a Kenyan refugee camp to Atlanta in 2001.
Keywords: Deng, Valentino Achak -- Fiction; Sudanese -- United States -- Fiction; Sudan -- History -- Civil War, 1983-2005 -- Fiction; Refugees -- Sudan -- Fiction; Refugees -- United States -- Fiction; Sudan -- Emigration and immigration -- Fiction; United States -- Emigration and immigration -- Fiction; Biographical fiction; Historical fiction